A randomized sham-controlled trial of transcranial and intranasal photobiomodulation in Japanese patients with mild cognitive impairment and mild dementia due to Alzheimer’s disease: a protocol - Yokoi, Yuma; Inagawa, Takuma; Yamada, Yuji; Matsui, Makoto; Tomizawa, Asumi; Noda, Takamasa (Frontiers in Neurology, 2024)
Introduction Photobiomodulation (PBM) is a novel strategy for cognitive enhancement by improving brain metabolism and blood flow. It is potentially beneficial for patients with Alzheimer’s disease (AD). We present a study protocol for a randomised controlled trial designed to evaluate the efficacy and safety of PBM. Method and analysis This is a single-centre, parallel-group, randomised, sham-controlled study. We enroll patients with mild cognitive impairment or dementia due to AD and assigned them to receive either active or sham stimulation at home for 12 weeks, with three sessions per week (20 min each). The stimulation involves invisible near-infrared light delivered by five applicators (one in a nostril, one on the frontal scalp, and three on the occipital scalp). The primary outcome will be the mean change in the Alzheimer Disease Assessment Scale-cognition from baseline to Week 12. We will also measure cognitive function, activity of daily living, behavioral and psychological symptoms, and caregiver burden. We will collect data at clinics at baseline and Week 12 and remotely at home. We estimate a sample size of 30 (20 active and 10 sham) based on an expected mean difference of −6.9 and an SD of 4.8. We use linear models for the statistical analysis. Ethics and dissemination The National Center of Neurology and Psychiatry Clinical Research Review Board (CRB3200004) approved this study. The results of this study will be published in a scientific peer-reviewed journal. Trial registration details Japan Registry of Clinical Trials jRCTs032230339.